Human Rights and Global Environment - Flora Pricilla Kalalo (Sociological Jurisprudence Journal, 2021)
Human rights and the environment are interconnected and mutually reinforcing. The concern of a group of people for the environment is not enough because changes in an environment have an impact not only locally, but often globally. Therefore it can be said that in countries where there are many violations of human rights, environmental damage often occurs. What happened then was that the human right to have a healthy life (the right to a healthy environment) was violated or sidelined. In addition, development that is not controlled can result in human rights being violated. Regulations regarding human rights are not entirely related to environmental protection. However, if you pay attention, there are several articles in some of these provisions that can be used as a legal basis for taking various actions aimed at protecting the environment. On the other hand, regulation of environmental protection at the same time means respect for human rights, especially with regard to issues of the right to life, health problems, disturbance of their property to respect for indigenous peoples' rights.